Estrategias para el control de plagas - García B, J.E. (International Center for Tropical Agriculture, 1979)
The principal terms used in pest control are discussed: the agrosystem, tolerance to pest damage (economic damage level and the economic threshold) and the general point of equilibrium (av population density of an insect). The methods used in insect control include cultural, mechanical, physical, biological chemical, genetic and regulation. None of these methods alone is sufficient to control pests; complementation or integrated control is recommended. (CIAT)